Cervical tuberculosis: a diagnostic dilemma in young mimicking cervical cancer - Bhardwaj, Bikram; Menon, Aruna; Singh, Randeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Genital tuberculosis (TB) is a disease that is still prevalent in third world countries but TB involving the cervix is a rare finding. It accounts for 0.1-0.65% of all cases of TB and nearly 5-10% cases of genital TB. Common presentation is persistent offensive vaginal discharge with either exophytic, ulcerative, interstitial or endo-cervical polypoidal growth over the cervix. We report here a rare presentation of cervical TB in young who presented with secondary amenorrhoea with ulcerative lesions over the cervix masquerading a cervical malignancy on local examination. Cervical biopsy revealed granulomatous cervicitis. The patient was managed with anti-TB treatment (ATT) for 6 months with resumption of menses and complete healing of the cervical lesion. Diagnosis of cervical TB is difficult clinically as it mimics an ulcerative variety of cancer cervix very closely. Confirmation is always by a cervical biopsy. This entity though rare can be entertained as a differential diagnosis in patients with cervical growth along with schistosomiasis, brucellosis and sarcoidosis.